Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Stres Kerja Sebagai Variabel Media-si PT Setia Alam Sinergi - Siska Nurma Pradhita; Suhana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of workload and work environment on employee performance through work stress as mediating variable at PT Setia Alam Sinergi Semarang. Population of the research are 107 employees. Census sampling technique is used in the research. For data analysis, outer model measurements were carried out. Inner model measurements and hypothesis testing by processing the data uses the Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. Research findings show that (1) work burden has a negative and significant effect on employee performance, (2) the work environment does not have significant effect on employee stress, (3) workload has a positive and significant effect on work stress, (4) the work environment has a negative and significant effect on work stress. (5) work stress has a negative and significant effect on employee performance, (6) work stress mediates the relationship between workload and employee performance, (7) work stress mediates the relationship between the working environment and employee performance.